Stress-dependent elastic properties of shales: measurement and modeling - Pervukhina, M.; Gurevich, Boris; Kuila, U.; Siggins, T.; Raven, M.; Bolas, H.; Dewhurst, D (Society of Exploration Geophysicists, 2008)
Despite decades of research, current understanding of elastic properties of shales is insufficient as it is based on a limited number of observations caused by the time-consuming nature of testing resulting from their low permeability. Though it is well known that shales are highly anisotropic and assumed to be transversely isotropic (TI) media, few laboratory experiments have been carried out for measuring the five elastic constants that define TI media on well-preserved shales. Many previous measurements were made without control of pore pressure, which is crucial for the determination of shale elastic properties.